2011
DOI: 10.1016/j.jnoncrysol.2010.11.100
|View full text |Cite
|
Sign up to set email alerts
|

Electrical switching studies on Ge–Te–Tl chalcogenide glasses: Effect of thallium on the composition dependence of switching voltages

Abstract: Bulk Ge 17 Te 83−x Tl x glasses (0 ≤ x ≤ 13), have been found to exhibit memory type electrical switching. The switching voltages (also known as threshold voltage -V th ) of Ge 17 Te 83−x Tl x glasses are found to decrease with increasing thallium content. The rate of decrease of V th is greater at lower concentrations and V th falls at a slower rate for higher thallium concentrations (x ≥ 6). The addition of thallium to the Ge-Te network fragments the covalent network and introduces ionic nature to it; the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
(58 reference statements)
3
18
0
Order By: Relevance
“…These pressures reflect a nearly linear decrease with the thallium content. Electrical switching [19] as well as ADSC and other studies [20,21] on this series of samples indicate that the thallium is present with two valencies, a trivalent thallium and a monovalent thallium. As a function of the thallium content, it is first incorporated as a Tl 3+ species but on further addition it is present as Tl 1+ .As the thallium content increases, the increasing monovalent species tends to fragment the network; this may lead to enhanced compression with the quasi-metallic transition occurring at lower pressures.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These pressures reflect a nearly linear decrease with the thallium content. Electrical switching [19] as well as ADSC and other studies [20,21] on this series of samples indicate that the thallium is present with two valencies, a trivalent thallium and a monovalent thallium. As a function of the thallium content, it is first incorporated as a Tl 3+ species but on further addition it is present as Tl 1+ .As the thallium content increases, the increasing monovalent species tends to fragment the network; this may lead to enhanced compression with the quasi-metallic transition occurring at lower pressures.…”
Section: Discussionsupporting
confidence: 62%
“…These samples were reported to undergo memory type of electrical switching. [19] Memory switching is accompanied by a phase change from amorphous to crystalline. The increase in Tl 1+ with composition was thought to aid this type of switching due its effect of fragmenting the network.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the earlier studies [22,23] reveal that thallium plays an interesting role in the Ge-Te-Tl glassy system, entering as two species with different valencies. It resides as a covalent Tl 3 + species at lower concentrations and as an ionic Tl 1 + at higher concentrations.…”
Section: Introductionmentioning
confidence: 94%
“…The effect of thallium on the glassy network has been central in understanding the composition dependence of the electrical switching and thermal parameters of Ge 17 Te 83 − x Tl x glasses [22,23]. It has been suggested that thallium enters the network with two types of valencies, as a trivalent Tl 3 + species which is covalent in nature and a monovalent Tl 1 + which is more ionic.…”
Section: The Composition Dependence Of Thermal Diffusivitymentioning
confidence: 99%
See 1 more Smart Citation